Promoting and Protecting Human Milk and Breastfeeding in a COVID-19 World - Spatz, Diane L.; Davanzo, Riccardo; Müller, Janis A.; Powell, Rebecca; Rigourd, Virginie; Yates, Ann; Geddes, Donna T.; van Goudoever, Johannes B.; Bode, Lars (Frontiers in Pediatrics, 2021)
The global COVID-19 pandemic has put enormous stress on healthcare systems and hospital staffing. However, through all this, families will continue to become pregnant, give birth, and breastfeed. Unfortunately, care of the childbearing family has been de-prioritized during the pandemic. Additionally, many healthcare practices during the pandemic have not been positive for the childbearing family or breastfeeding. Despite recommendations from the World Health Organization to promote early, direct breastfeeding and skin to skin contact, these and other recommendations are not being followed in the clinical setting. For example, some mothers have been forced to go through labor and birth alone in some institutions whilst some hospitals have limited or no parental visitation to infants in the NICU. Furthermore, hospitals are discharging mothers and their newborns early, limiting the amount of time that families receive expert lactation care, education, and technical assistance. In addition, some hospitals have furloughed staff or transferred them to COVID-19 wards, further negatively impacting direct care for families and their newborns. We are concerned that these massive changes in the care of childbearing families will be permanently adopted. Instead, we must use the pandemic to underscore the importance of human milk and breastfeeding as lifesaving medical interventions. We challenge healthcare professionals to change the current prenatal and post birth practice paradigms to protect lactation physiology and to ensure that all families in need receive equal access to evidence-based lactation education, care and technical assistance.